Mathematics 2011 | Study Mode

Join Discuss Share to WhatsApp
Question 11
A
2X - 1
B
X + 3
C
2X + 1
D
X - 3
Explanation
X2 + 1 \(\frac{X - 2}{\sqrt{X^3 - 2X^2 + 3n - 3}}\)

= \(\frac {- 6X^3 + n}{-2X^2 + 2X - 3}\)

= \(\frac{(-2X^2 - 2)}{2X - 1}\)

Remainder is 2X - 1

Correct option: A
Join Discuss Share to WhatsApp
Question 12
A
(3y - 2x)(3y + 4x)
B
(3y + 4x)(3y + 4x)
C
(3y + 2x)(3y - 4x)
D
(3y - 4x)(3y + 4x)
Explanation
9y2 - 16x2

= 32y2 - 42x2

= (3y - 4x)(3y +4x)

Correct option: D
Join Discuss Share to WhatsApp
Question 13
A
-3, -9
B
9, -3
C
-9,3
D
3, -9
Explanation
-2x -5y = 3

x + 3y = 0

x = -3y

-2 (-3y) - 5y = -3

6y - 5y = 3

y = 3

but, x = -3y

x = -3(3)

x = -9

therefore, x = -9, y = 3

Correct option: C
Join Discuss Share to WhatsApp
Question 14
A
20\(\frac{1}{4}\)
B
27
C
2\(\frac{1}{4}\)
D
36
Explanation
x \(\alpha\sqrt y\)

x = k\(\sqrt y\)

81 = k\(\sqrt9\)

k = \(\frac{81}{3}\)

= 27

therefore, x = 27\(\sqrt y\)

y = 1\(\frac{7}{9}\) = \(\frac{16}{9}\)

x = 27 x \(\sqrt{\frac{16}{9}}\)

= 27 x \(\frac{4}{3}\)

dividing 27 by 3

= 9 x 4

= 36

Correct option: D
Join Discuss Share to WhatsApp
Question 15
A
\(\frac{1}{18}\)
B
\(\frac{1}{12}\)
C
\(\frac{1}{24}\)
D
\(\frac{1}{6}\)
Explanation
T \(\alpha \frac{1}{R^3}\)

T = \(\frac{k}{R^3}\)

k = TR3

= \(\frac{2}{81}\) x 33

= \(\frac{2}{81}\) x 27

dividing 81 by 27

k = \(\frac{2}{2}\)

therefore, T = \(\frac{2}{3}\) x \(\frac{1}{R^3}\)

When R = 2

T = \(\frac{2}{3}\) x \(\frac{1}{2^3}\) = \(\frac{2}{3}\) x \(\frac{1}{8}\)

= \(\frac{1}{12}\)

Correct option: B
Join Discuss Share to WhatsApp
Question 16
A
x \(\leq\) 2
B
x \(\geq\) -1
C
x \(\geq\) -2
D
x \(\leq\) -1
Explanation
-6(x + 3) \(\leq\) 4(x - 2)

-6(x +3) \(\leq\) 4(x - 2)

-6x -18 \(\leq\) 4x - 8

-18 + 8 \(\leq\) 4x +6x

-10x \(\leq\) 10x

10x \(\leq\) -10

x \(\leq\) 1

Correct option: B
Join Discuss Share to WhatsApp
Question 17
A
x < -3 or x > 5
B
-5 < x < 3
C
x < 3 or x > 5
D
x > 3 or x < -5
Explanation
x2 + 2x > 15

x2 + 2x - 15 > 0

(x2 + 5x) - (3x - 15) > 0

x(x + 5) - 3(x + 5) >0

(x - 3)(x + 5) > 0

therefore, x = 3 or -5

then x < -5 or x > 3

i.e. x< 3 or x < -5

Correct option: D
Join Discuss Share to WhatsApp
Question 18
A
505
B
513
C
433
D
635
Explanation
3, 6, 9,..., 36.

a = 3, d = 3, i = 36, n = 18

Sn = \(\frac{n}{2}\) [2a + (n - 1)d

S18 = \(\frac{18}{2}\) [2 x 3 + (18 - 1)3]

= 9[6 + (17 x 3)]

= 9 [6 + 51] = 9(57)

= 513

Correct option: B
Join Discuss Share to WhatsApp
Question 19
A
60
B
62
C
54
D
64
Explanation
T2 = 4, T4 = 16

Tx = arn-1

T2 = ar2-1 = 4 i.e. ar3 = 16, i.e. ar = 4

T4 = ar4-1

therefore, \(\frac{T_4}{T_r}\) = \(\frac{ar^3}{ar}\) = \(\frac{16}{4}\)

r2 = 4 and r = 2

but ar = 4

a = \(\frac{4}{r}\) = \(\frac{4}{2}\)

a = 2

Sn = \(\frac{a(r^n - 1)}{r - 1}\)

S5 = \(\frac{2(2^5 - 1)}{2 - 1}\)

= \(\frac{2(32 - 1)}{2 - 1}\)

= 2(31)

= 62

Correct option: B
Join Discuss Share to WhatsApp
Question 20
A
- \(\frac{1}{2}\)
B
\(\frac{1}{3}\)
C
-1
D
2
Explanation
N + Y = XY + X + Y

3 + -\(\frac{2}{3}\) = 3(- \(\frac{2}{3}\)) + 3 + (- \(\frac{2}{3}\))

= -2 + 3 -\(\frac{2}{3}\)

= \(\frac{1 - 2}{1 - 3}\)

= \(\frac{1}{3}\)

Correct option: B

Try this quiz in in E-test/CBT Mode
switch to Mathematics 2011 in CBT Mode

Previous Page Next Page